2012
DOI: 10.1002/adhm.201200030
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable Photo‐Crosslinked Polymer Substrates with Concentric Microgrooves for Regulating MC3T3‐E1 Cell Behavior

Abstract: Both intrinsic material properties and topographical features are critical in influencing cell-biomaterial interactions. We present a systematic investigation of regulating mouse pre-osteoblastic MC3T3-E1 cell behavior on biodegradable polymer substrates with distinct mechanical properties and concentric microgrooves. The precursors for fabricating substrates used here were two poly(ϵ-caprolactone) triacrylates (PCLTAs) synthesized from poly(ϵ-caprolactone) triols with molecular weights of ∼7000 and ∼10000 g m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
54
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 42 publications
(64 citation statements)
references
References 46 publications
10
54
0
Order By: Relevance
“…BMP‐2 is well known as a strong inducer of bone formation, which has been demonstrated to potently induce the differentiation of a variety of cell types into osteoblast precursors . Interestingly, it was observed that the proliferative roles of proliferative agents (FGF‐2) were interfered by BMP‐2 when they existed together in cell culture.…”
Section: Discussionmentioning
confidence: 99%
“…BMP‐2 is well known as a strong inducer of bone formation, which has been demonstrated to potently induce the differentiation of a variety of cell types into osteoblast precursors . Interestingly, it was observed that the proliferative roles of proliferative agents (FGF‐2) were interfered by BMP‐2 when they existed together in cell culture.…”
Section: Discussionmentioning
confidence: 99%
“…The MC3T3 E1 cell line has been used extensively to evaluate bone templates including HAP nanocomposites and electrospun fibers . As confirmed by Wutticharoenmongkol et al, PCL nanofibers alone does not provide a sufficient microenvironment for MC3T3 E1 cells to secrete bone matrix or promote mineralization.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have found that fiber diameter and fiber surface structure can influence cell behavior . PCL substrates with concentric microgrooves have shown the ability to regulate MC3T3‐E1 cell behavior . After introducing kebabs on the PCL nanofiber surface, the fiber diameter and surface structure—both chemical and morphological—have changed.…”
Section: Cytocompatibility Of Nfsksmentioning
confidence: 99%
“…48 PCL substrates with concentric microgrooves have shown the ability to regulate MC3T3-E1 cell behavior. 49 After introducing kebabs on the PCL nanofiber surface, the fiber diameter and surface structure-both chemical and morphological-have changed. Therefore, it is of interest to study the influence of this surface modification on cell growth and attachment to the NFSK surface.…”
Section: Cytocompatibility Of Nfsksmentioning
confidence: 99%